WARDANDI BOODJA: TRUTH-TELLING - Andrews, Stuart Gordon (Curtin University, 2022)
This exegesis is an art and reconciliation response to the Uluru Statement From the Heart. Wardandi Nyungar Elders, Bill, and Nina Webb inform this project of the 1841 Wonnerup/Minninup massacre. Action Research informs the use of Yarning, decolonisation, and collaboration to hear alternative historical narratives. The project culminated in public art and truth-telling workshops to learn and heal together. I ask can art and yarning assist with historical truth-telling and reconciliation.